The Typology of Pesantren’s Islamic Thoughts in Java: A Qualitative Study - Ikhsanudin, Muhammad; Syamsuddin, Sahiron; Sunarwoto, Sunarwoto (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to present a typology of Pesantren in the current modern era based on the basic ideas of each Pesantren. This study is essential as part of efforts to dynamize the development of Pondok Pesantren in Indonesia. Design/methods/approach – Descriptive qualitative study is the method used in this research. The informants in this study are the leaders of Islamic boarding schools across Java. The data collection process uses in-depth interviews, participatory observation, and documentation. The data analysis process is based on Milles Huberman’s data analysis. Findings – The typology formed from the results of observations is that there are three Pesantren, namely the first Pesantren, which remains restraining learning and preserves the classical Islamic inheritance with all educational instruments. Second, Pondok Pesantren accommodates the two mainstreams of thought, the social modernity and the social-humanity tradition, by founding official/formal schools or education and combining two intellectual traditions between Islamic tradition and Western tradition. Third, Pondok Pesantren developed the learning towards religious books or Kitab Kuning beyond the initial basis of the madhab era (The era of the school of scientific thought about Muslim laws). Research implications/limitations – this research has implications for developing the broader characteristics of Islamic boarding schools. In addition, a complete understanding of the Islamic Boarding School was obtained. This study has limitations in the aspects observed. This study only observes the type of Islamic Boarding School typology seen from the form of educational thought that is developed. Practical implications – This study provides a newer perspective regarding the typology of developing Pesantren and explains the importance of the role of Pesantren in the discourse of Islamic education in Indonesia.